Halotolerant Plant Growth-Promoting Rhizobacteria Isolated From Saline Soil Improve Nitrogen Fixation and Alleviate Salt Stress in Rice Plants - Khumairah, Fiqriah Hanum; Setiawati, Mieke Rochimi; Fitriatin, Betty Natalie; Simarmata, Tualar; Alfaraj, Saleh; Ansari, Mohammad Javed; Enshasy, Hesham A. El; Sayyed, R. Z.; Najafi, Solmaz (Frontiers in Microbiology, 2022)
Salinity is one of the most damaging abiotic stresses due to climate change impacts that affect the growth and yield of crops, especially in lowland rice fields and coastal areas. The present research aimed to isolate potential halotolerant plant growth-promoting rhizobacteria (PGPR) from different rhizo-microbiome and use them as effective bioinoculants to improve rice growth under salinity stress conditions. Bioassay using rice seedlings was performed in a randomized block design consisting of 16 treatments (control and 15 bacteria isolates) with three replications. Results revealed that isolates S3, S5, and S6 gave higher shoot height, root length, and plant dry weight compared to control (without isolates). Based on molecular characteristics, isolate S3 and S5 were identified as Pseudomonas stutzeri, and Klebsiella pneumonia worked as halotolerant plant growth-promoting rhizobacteria to promote rice growth under salinity stress conditions. These three potent isolates were found to produce indole-3-acetic acid (IAA) and nitrogenase.